Traiettorie di sistema in un “campo” variantistico: A Boris Pasternak di Franco Fortini - Fichera, Gabriele (L'ospite ingrato, 2025)
This essay attempts to explore the variants of Fortini’s poem A Boris Pasternak. The compositional process of the text appears particularly rich and complex, as attested by the two related unpublished typescripts, to which systematic reference is made throughout these pages. Taken together, these movements allow us to speak of a veritable “field” of variants endowed with a significant degree of coherence. Its main vectors can be recognized by four typologies, classified as follows: variants of “acquisition”, “loss”, “circular” and “antithetical”. Through the reconstruction of this network of variants, the essay also brings to light a varied intertextual dialogue which, although often taking place in absentia, is somehow reflected in the meaning of the definitive text.